2010
DOI: 10.1021/jp107313r
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect of Ti−Li−N Compounds in the Li−N−H System on Hydrogen Desorption Properties

Abstract: Three types of compounds (Li 5 TiN 3 , Li 5 TiN 3 (NH 3 ) x , and TiCl 3 (NH 3 ) x ) were synthesized as possible catalysts in the Li-N-H system, and their catalytic effects on hydrogen desorption performance were examined. The three types of compounds exhibited a catalytic effect in the Li-N-H system. The XRD results and the ball milling time indicate that the particle size may be one of the important factors for hydrogen desorption properties acting as effective catalyst. Furthermore, on the basis of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In addition, the formation of TiCl 3 •5NH 3 and TiCl 3 •3NH 3 was further confirmed by elemental analysis, which gave the ratio of Ti/N = 1:5 for TiCl 3 •5NH 3 and Ti/N = 1:3 for TiCl 3 •3NH 3 , respectively. The high-resolution XRD profiles of TiCl 3 •nNH 3 (n = 3 and 5), which are consistent with a previous report, 15 are shown in Figure S2 in the Supporting Information. These ammine titanium borohydrides were prepared by ball milling the mixtures of TiCl 3 •3NH 3 /TiCl 3 •5NH 3 −LiBH 4 (in molar ratios of 1:3, 1:4, and 1:5) using Planetary QM-3SP2 with a ball-to-sample ratio of 30:1, agitation frequency of 350 rpm.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the formation of TiCl 3 •5NH 3 and TiCl 3 •3NH 3 was further confirmed by elemental analysis, which gave the ratio of Ti/N = 1:5 for TiCl 3 •5NH 3 and Ti/N = 1:3 for TiCl 3 •3NH 3 , respectively. The high-resolution XRD profiles of TiCl 3 •nNH 3 (n = 3 and 5), which are consistent with a previous report, 15 are shown in Figure S2 in the Supporting Information. These ammine titanium borohydrides were prepared by ball milling the mixtures of TiCl 3 •3NH 3 /TiCl 3 •5NH 3 −LiBH 4 (in molar ratios of 1:3, 1:4, and 1:5) using Planetary QM-3SP2 with a ball-to-sample ratio of 30:1, agitation frequency of 350 rpm.…”
Section: Methodssupporting
confidence: 91%
“…In addition, the formation of TiCl 3 ·5NH 3 and TiCl 3 ·3NH 3 was further confirmed by elemental analysis, which gave the ratio of Ti/N = 1:5 for TiCl 3 ·5NH 3 and Ti/N = 1:3 for TiCl 3 ·3NH 3 , respectively. The high-resolution XRD profiles of TiCl 3 · n NH 3 ( n = 3 and 5), which are consistent with a previous report, are shown in Figure S2 in the Supporting Information.…”
Section: Methodssupporting
confidence: 91%
“…For the composite without an additive, two broad-shaped hydrogen desorption curves and obvious ammonia emission are observed, which is in good agreement with the previous reports. [9][10][11][12] Interestingly, a signicant enhancement of dehydrogenation properties is achieved by introducing KOH into the LiNH 2 -LiH system, whereas the hydrogen desorption behaviours of the LiOH-or NaOH-doped composites have no obvious change. In comparison with the broad shaped hydrogen desorption curve of the composite without an additive, the hydrogen desorption curve of the LiNH 2 -LiH-0.05KOH composite becomes narrow.…”
Section: The Dehydrogenation Properties Of the Alkali Metal Hydroxide...mentioning
confidence: 99%
“…Various efforts have been devoted for improving its hydrogen absorption and desorption kinetics. [9][10][11][12][13][14][15][16][17][18][19] Additives, such as titanium compounds, metal borohydrides, metal oxides and carbon-based materials were determined to be effective in improving the hydrogen storage properties of the LiNH 2 -LiH system.…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations have been proved that mixing other additives into the LiNH 2 eLiH composite is effect to improving its hydrogen storage properties [12e18]. Teng et al found that Ti compound has a catalytic effect on LieNeH system, due in part to the possible Li 5 TN 3 (NH 3 )x intermediate [12]. Metal oxide reported by Zhang et al shows a catalytic effect on improving the hydrogen storage performance of the LithiumeHydrogeneNitrogen system [13,18].…”
Section: Introductionmentioning
confidence: 99%